Exposure to outdoor artificial light at night and breast cancer risk: a population-based case-control study in two French departments (the CECILE study) - Prajapati, Nirmala; Cordina-Duverger, Emilie; Boileau, Adélie; Faure, Elodie; Guénel, Pascal (Frontiers in Environmental Health, 2023)
Background Exposure to outdoor artificial light at night (LAN) disrupts circadian rhythms and is suspected of increasing the risk of breast cancer. To date, this is an understudied aspect of environmental pollution. In this study, we sought to assess the specific role of exposure to outdoor artificial light at night in breast cancer, independently of air pollution-related effects. Methods Data from a French population-based case‒control study, including 1185 incident breast cancer cases and 1282 controls enrolled in 2005-2007, were used. Outdoor LAN exposure data were obtained using radiance-calibrated images from the Defense Meteorological Satellite Program (DMSP) for 1995-2006 by cross-referencing the DMSP images and the geocoded locations of residences in ArcGIS. The odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were obtained using logistic regression adjusting for multiple potential confounders, including air pollution. Results The OR for overall breast cancer unadjusted for air pollution per interquartile range increase in LAN exposure was 1.05 (95% CI: 0.92-1.20). The OR decreased to 0.98 (95% CI: 0.81-1.17) after adjustment for ambient NO2 levels. Subgroup analyses showed slightly higher ORs in postmenopausal women (OR per IQR increase: 1.07; 95% CI: 0.85-1.35) and a positive association for HER2-positive breast tumors (OR: 1.55; 95% CI: 1.03-2.31). Conclusion Our results do not provide evidence that outdoor LAN exposure is associated with increased risk of breast cancer. However, an association was suggested for the HER2-positive subtype of breast cancer. Further large-scale studies with more precise exposure assessment methods, including blue light and indoor exposure measurements, and considering environmental exposures correlated with LAN exposure such as air pollution, are needed.